The Construction of narratives about the past. Advocacy for history - Álvaro Dueñas, Manuel (Universidad Pedagógica y Tecnológica de Colombia, 2020)
For some time, we have been witnessing a resurgence in the use of the past to legitimize exclusionary identitarian discourses as well as imaginary and often apocalyptic narratives about the world. The expansion of cultural relativism even reaches science denialism. The present article analyzes some recent cases of confronted, re-written or conflict-themed narratives, and connections are made with the discourses of historiography from its controversial theories and methodologies. The potential of history as a social science to refute historicist doctrinal constructions that attempt to legitimize the structures and the hegemonic relationships of power is shown. It is argued how history, as a social science, builds methodical, and therefore, critical knowledge, and it is concluded that said knowledge limits ideological preconceptions and dismantles the arbitrariness of the organic narratives that manipulate, decontextualize and twist the past, to the extent of denaturing and mythicizing it.